Sosialisasi Pemanfaatan Sampah Menjadi Produk Daur Ulang Untuk Meningkatkan Kesadaran Lingkungan Pada Masyarakat - Ramadianti, Astria Ayu; Hidayat, Wahyu; Putri, Nizmi; Safitri, Layil; Ramadhan, Nuri; Hariaty, Emy; Malinda, Leni; Ramadhani, Mastari; Harahap, Syarifah Ainun; Lubis, Rizka Hidayah Husin; Herdyana, Thessa (Jurnal Pengabdian Masyarakat, 2025)
Waste management is a crucial component in maintaining environmental sustainability. Furthermore, the current environment is facing an environmental crisis. Rapid urban population growth and consumption patterns have led to an unprecedented increase in waste generation, posing significant challenges to the waste management system. This community service activity focused on promoting the utilization of waste into recycled products to raise environmental awareness in the community. All activities, including pre-implementation, implementation of waste management socialization, and monitoring, were successfully implemented. This activity demonstrates that the effort has successfully increased public knowledge and awareness of the environment.